Peran Pesantren Al-Zaytun Dalam Implementasi Moderasi Beragama - sobirin; Santoso, Budi (Al-Manaj : Jurnal Program Studi Manajemen Dakwah, 2025)
Every individual should respect the beliefs of others without demeaning or insulting them. The practice of religious moderation can be carried out by individuals, community groups, and even educational institutions. In this study, Al-Zaytun is an educational institution that practices religious moderation in accordance with Pancasila values. The research uses a literature study model, utilizing library data presented descriptively to analyze phenomena and events in a particular environment. The aim of the study is to deeply and comprehensively explore the role of Pesantren Al-Zaytun in implementing religious moderation. The findings reveal that Pesantren Al-Zaytun consistently instills in its students the importance of respecting religious differences and regularly invites interfaith leaders to events held at the pesantren, such as during the celebration of Satu Syuro. However, limited public understanding of religious moderation presents a challenge for Al-Zaytun, as its practices are perceived as unconventional or even heretical by some. Nevertheless, support from interfaith leaders continues to strengthen the implementation of religious moderation at the pesantren.